Total Synthesis of DHA and DPAn-3 Non-Enzymatic Oxylipins - Guy, Alexandre; Merad, Jérémy; Degrange, Thomas; Reversat, Guillaume; Bultel-Poncé, Valérie; Durand, Thierry; Galano, Jean-Marie; Oger, Camille (Synthesis, 2021)
Oxylipins are formed in vivo from polyunsaturated fatty acids (PUFAs). A large structural variety of compounds is grouped under the term oxylipins, which differ from their formation mechanism (involving enzymes or not), as well as their chemical structures (cyclopentane, tetrahydrofuran, hydroxylated-PUFA, etc.). All structures of oxylipins are of great biological interest. Directly correlated to oxidative stress phenomenon, non-enzymatic oxylipins are used as systemic and/or specific biomarkers in various pathologies, and more especially, they were found to have their own biological properties. Produced in vivo as a non-separable mixture of isomers, their total synthesis is a keystone to answer biological questions. In this work, the total synthesis of three non-enzymatic oxylipins derived from docosahexaenoic acid (DHA) and docosapentanoic acid (DPAn-3) is described using a unique and convergent synthetic strategy.
Keywords: total synthesis; oxidative stress; biomarkers; neuroprostanes; non-enzymatic oxylipins